Antara Tradisi dan Transformasi: Dialektika Islam dan Budaya Melayu dalam Membangun Pendidikan di Era Modern - Anin Fikriyah; Sri Pujiati; Maryamah Maryamah; Choirun Niswah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The tension between preserving Islamic-Malay tradition and the demands of modern educational transformation is a fundamental challenge for Islamic education institutions in the contemporary era. This study aims to systematically analyze the dialectics between Islamic tradition and Malay culture in building education in the modern era, focusing on mapping transformation patterns, identifying conceptual tensions, and formulating an adaptive integration model. This research employs a qualitative approach with a Systematic Literature Review (SLR) design guided by the PRISMA 2020 framework. The study population consisted of scientific articles indexed in Google Scholar, Scopus, and SINTA, with a purposive sampling technique applied based on explicit inclusion and exclusion criteria. Data were extracted using a structured extraction sheet and analyzed through thematic synthesis. From 184 identified articles, 25 met the full inclusion criteria. Results reveal five consistent themes: adaptive institutional transformation, Islamic-Malay identity as dynamic social capital, the dual impact of globalization, integration of Malay cultural values in curriculum, and the dominance of single-context studies. This study concludes that tradition and transformation function as mutually reinforcing dialectical forces, and proposes the concept of a dialectical integrative model as a pedagogical framework for building relevant and characterful Islamic education.